Survival and prognostic factors in patients with Non-Small Cell Lung Cancer treated in private health care - Araujo,Luiz Henrique de Lima (2014)
INTRODUCTION: Outcomes data on Non-Small Cell Lung Cancer (NSCLC) are scarce with regard to the private health care in Brazil. The aim of this study was to describe the characteristics, treatments performed, and the survival of patients with NSCLC in a Brazilian private oncologic institution. METHODS: Medical charts from patients treated between 1998 and 2010 were reviewed, and data were transferred to a clinical research form. Long-term follow-up and survival estimates were enabled through active surveillance. RESULTS: Five hundred sixty-six patients were included, and median age was 65 years. Most patients were diagnosed in advanced stages (79.6% III/IV). The overall survival was 19.0 months (95%CI 16.2 - 21.8). The median survival was 99.7, 32.5, 20.2, and 13.3 months for stages I, II, III, and IV, respectively (p < 0.0001). Among patients receiving palliative chemotherapy, the median survival was 12.2 months (95%CI 10.0 - 14.4). CONCLUSIONS: The outcomes described are favorably similar to the current literature from developed countries. Besides the better access to health care in the private insurance scenario, most patients are still diagnosed in late stages.